Correction to: Discovery and preclinical characterization of the antagonist anti-PD-L1 monoclonal antibody LY3300054. Issue 1 (4th June 2018) - Li, Yiwen; Carpenito, Carmine; Wang, George; Surguladze, David; Forest, Amelie; Malabunga, Maria; Murphy, Mary; Zhang, Yiwei; Sonyi, Andreas; Chin, Darin; Burtrum, Douglas; Inigo, Ivan; et al.
Abstract : Unfortunately, after publication of this article [1], it was noticed that corrections to the legends of Figs. 1 and 2 were not correctly incorporated. The correct legends can be seen below.